Effects of oppositely charged moieties on the self-assembly and biophysicochemical properties of polyurethane micelles. Issue 23 (20th May 2022) - Pan, Zhicheng; Yang, Guangxuan; Liu, Jian; Yuan, Jinfeng; Pan, Mingwang; Li, Jiehua; Tan, Hong
Abstract : The interchain electrostatic attraction by oppositely charged moieties severely disturbs the function of GQA in micelles, leading to poor self-assembly, micellization, and stabilization. Longer mPEG chain cannot fully alleviate this negative effect. Abstract : Gemini quaternary ammonium (GQA), a type of cationic surfactant, exhibits excellent micellization ability and acts as a cell internalization promoter to increase the permeability of the cell membrane. GQA is sensitive to ionic solutions, which disturb its stabilization and leads to the rapid degradation of its polymer micelles due to its unique hydrophilic N + structure. However, the effect of negatively charged moieties in the polymer chains of GQA on its action in polymer micelles, typically with regard to its micellization and biological performance, remains unclear. In this work, a series of polyurethane micelles containing various ratios of oppositely charged moieties was prepared. We found that the interchain electrostatic interaction severely undermines the function of the GQA surfactant and hinders the self-assembly and stabilization of polyurethane micelles. Specifically, a hydrophilic corona with a longer length cannot completely overcome this effect. By regulating the ratio of oppositely charged moieties, micelles exhibited tunable biological properties, such as biocompatibility, cytotoxicity, cell internalization, and phagocytosis by macrophages. Based on our results, a moderate molecular weight of mPEG (Mn = 1900) and a slight positive surface potential (∼10 mV) are the best surface parameters for the comprehensive performance of the studied nanoplatforms. This study provides a further understanding of the electrostatic interaction effect on the properties of the cationic GQA, offering rational guidance for the design and fabrication of GQA polymer micelles.